Hydrogeochemical characterization of the urban coastal aquifers of Napoli (southern Italy): an overview - Corniello, Alfonso; Ducci, Daniela (Acque Sotterranee - Italian Journal of Groundwater, 2019)
The presence of phenomena of salt water intrusion in aquifers located in coastal urbanized areas, especially depended on the use of groundwater, is a widespread problem in the world. The study deals with the large coastal belt of the Municipality of Naples(southern Italy), located between the volcanic areas of the Somma-Vesuvius (East) and the Phlegrean Fields (West). Three different coastal sectors were analysed: the plain of Bagnoli-Fuorigrotta (BF), the area of Mount Echia (E) and the area of Eastern Naples (EN). Acquired chemical data allowed of the identification of three different groundwater chemical features and the prevalent absence of sea water contamination, mainly due to the low use of these waters. The study highlighted the chief role of the presence of faults in this volcanic area, favouring the upwelling of gases (prevalently CO2). These gases increase the groundwater reactivity causing, in the Mount Echia sector, the presence of sulphurous mineral waters and, in the Bagnoli-Fuorigrotta sector, determining the alteration of the natural relationship between freshwater and saltwater. Moreover, in the Eastern Naples sector, the occurrence of lenses of peat, which play an important hydrogeologic role as aquiclude, can determine reducing condition in the aquifers, with high concentrations in Fe and Mn.